THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY IN ISLAMIC BANKS WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Ishak, Muhammad Zakiy; Azzahroh, Evrita Putri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2017)
This research aims to examine the role of customer satisfaction as a mediating variable to connecting service quality to customer loyalty in Islamic Banks. This study also tested compliance as the dimension for measure quality service in Islamic Bank. This research was conducted in five Islamic Banks which are in Indonesia. Data were collected using a questionnaire, distributed through are online and offline to the Islamic Bank customer. There are 100 questionnaires were successfully collected and analyzed using Structural Equation Modeling (SEM) to test the hypothesis with the application of Smart-PLS 3.0. the result of this study indicate that customer satisfaction is able to mediate (full mediation) in influence the service quality to customer loyalty in Islamic Banks.